To Lessen Copper Pin Loss in the Electronics Sector Evaluate and Enhance the Copper Pin Sorting Machine's Performance - Chuchotsakunleot, Arithat (Mechanical Technology and Engineering Insights, 2025)
This article discusses the enhancement of the copper pin alignment process through several methods: reducing the size of the fixtures, adjusting the angles of each fixture, and increasing the height of the copper pins at the joints of sections 1 to 4 while cutting the copper pins feeding into the stainless-steel tray. During a 26-day trial, each machine produced 7,176,000 copper pins from 2,990 boats. Machine 1 resulted in 33,961 defective copper pins, which is 0.47%, leading to an inability to produce 16,981 diodes. With an average price of 12 baht per diode, this caused a revenue loss of 203,772 baht. In comparison, Machine 2, which is a new model, had 21,176 defective copper pins, or 0.29%, affecting the production of 10,588 diodes and resulting in a revenue loss of 127,056 baht. Machine 3, also a new model, recorded 14,148 defective copper pins, which is 0.19%, equivalent to a loss of 7,074 diodes and a revenue loss of 84,888 baht.  In terms of energy consumption, the first copper pin machine uses 720.72 Kwh, resulting in an annual electrical cost of approximately 3,012.61 baht. Both the new copper pin sorting machine 2 and machine 3 consume 288.288 Kwh, translating to an annual cost of about 1,205.04 baht each. This change significantly reduces copper pin loss and leads to electricity savings.